Cosmic ray event of A.D. 774–775 shown in quasi‐annual 10Be data from the Antarctic Dome Fuji ice core. Issue 1 (8th January 2015) - Miyake, Fusa; Suzuki, Asami; Masuda, Kimiaki; Horiuchi, Kazuho; Motoyama, Hideaki; Matsuzaki, Hiroyuki; Motizuki, Yuko; Takahashi, Kazuya; Nakai, Yoichi
Abstract 14C content in tree rings and 10Be concentration records in polar ice core provide information about past cosmic ray intensities. The A.D. 774–775 cosmic ray event has been identified by 14C measurement in several tree rings from all over the world. Although the quasi‐decadal 10Be Dome Fuji data in the Antarctic ice core also shows a sharp peak around A.D. 775, annual 10Be variations in the Dome Fuji core or in other cores have not been revealed. We have measured quasi‐annual 10Be concentrations from approximately A.D. 763–794 in the Dome Fuji ice core, and detected a clear increase (~80% above the baseline) in 10Be concentration around A.D. 775. However, an accurate height of this increase is not straightforwardly estimated due to the background variation in 10Be concentration. The 10Be increase can be due to the same cosmic ray event as shown in the 14C content in A.D. 774–775.